2007
DOI: 10.1103/physrevlett.98.067002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Superconductivity and Evidence of Structural Instability in Intercalated GraphiteCaC6under High Pressure

Abstract: We measured the temperature dependent resistivity, varrho(T), of the intercalated graphite superconductor CaC6 as a function of pressure up to 16 GPa. We found a large linear increase of critical temperature, Tc, from the ambient pressure value 11.5 K up to 15.1 K, the largest value for intercalated graphite, at 7.5 GPa. At approximately 8 GPa, a jump of varrho and a sudden drop of Tc down to approximately 5 K indicates the occurrence of a phase transition. Our data analysis suggests that a pressure-induced ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
122
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 18 publications
13
122
0
Order By: Relevance
“…For YbC6 this occurs at approximately 2 GPa whilst in CaC6 this occurs at approximately 8 GPa. In the case of CaC6 there was a suggestion [35] that the decrease can be attributed to a structural transition and a subsequent paper confirmed an order to disorder transition at this pressure with no apparent change in space group [36]. This onset of disorder is consistent with the interpretation of the increase in residual resistivity reported in [35].…”
Section: Superconducting Phase Diagramssupporting
confidence: 72%
See 1 more Smart Citation
“…For YbC6 this occurs at approximately 2 GPa whilst in CaC6 this occurs at approximately 8 GPa. In the case of CaC6 there was a suggestion [35] that the decrease can be attributed to a structural transition and a subsequent paper confirmed an order to disorder transition at this pressure with no apparent change in space group [36]. This onset of disorder is consistent with the interpretation of the increase in residual resistivity reported in [35].…”
Section: Superconducting Phase Diagramssupporting
confidence: 72%
“…In order to search for any trends several groups have made a number of measurements to explore the impact of pressure. Figure 1.4 presents the pressure phase diagrams for both YbC6 [34] and CaC6 [35]. In addition the pressure dependence of Tc in SrC6 is presented in the inset plot in This difference is the point at which the transition temperature begins to decrease.…”
Section: Superconducting Phase Diagramsmentioning
confidence: 99%
“…The measured T c (P )-dependence is seen to be reversible and not depend on the temperature at which the pressure is changed. Within experimental error the rate of increase, dT c /dP ≈ +0.40(1) K/GPa, is the same for both samples, but 5 -10 % less than that reported previously in experiments where less hydrostatic pressure media were used [3,4,6].…”
Section: Methodssupporting
confidence: 55%
“…This relatively large positive value of the initial slope dT c /dP stands in contrast to the negative dependence normally found in s, p-electron metals which superconduct at ambient pressure [5]. An electrical resistivity study on CaC 6 to 16 GPa using Fluorinert pressure medium reported that T c initially increases under pressure at the rate ∼ +0.5 K/GPa, reaching a maximum value of 15.1 K before dropping abruptly at 9 GPa to ∼ 5 K, apparently due to a first-order structural phase transition [6]. Recent room-temperature synchrotron x-ray diffraction studies to 13 GPa using helium or argon pressure media report the onset of reversible peakbroadening above 9 GPa which is interpreted as giving evidence for an unusual orderdisorder phase tranformation with no change in space group symmetry from R3m rhombohedral [7].…”
Section: Introductionmentioning
confidence: 86%
“…The ground states of graphitic materials can be metallic, semi-metallic or semiconducting, depending on the allotrope form or intercalated species, and some have even been shown to superconduct 2,3 with transition temperatures (T c ) above 10 K (ref. 4,5).…”
mentioning
confidence: 99%